Impacts of national volume-based drug procurement policy on the utilization and costs of antihypertensive drugs in a Chinese medicine hospital: an interrupted time series analysis of 5138 patients - Lili Shang; Lili Shang; Yan Cheng; Jifang Zhou; Yuqing Bao; Desong Kong; Ruijian Huang; Yanfei Chen; Hao Wang; Hao Wang; Ning Gu; Aixia Ma (Frontiers Media S.A., 2024)
Objectives: The study aimed to estimate the effects of National Volume-based Drug Procurement (NVBP) policy on drug utilization and medical expenditures of hypertension patients in public medical institutions in mainland China.Methods: This study used patient-level data based on electronic health records retrieved from the hospital information system of Nanjing Hospital of Chinese Medicine. Data on patients with hypertension who received care at this institution between 2016 and 2021 was used for analysis. Segmented linear regression models incorporating Interrupted Time Series (ITS) analysis were adopted to examine the effects of NVBP policy on drug utilization and health expenditures of eligible patients. Drug utilization volume and health expenditures were the primary outcomes used to assess the policy effects, and were measured using the prescription proportion of each drug class and the overall per-encounter treatment costs.Results: After the implementation of NVBP policy, the volume of non-winning drugs decreased from 54.42% to 36.25% for outpatient care and from 35.62% to 15.65% for inpatient care. The ITS analysis showed that the volume of bid-winning drugs in outpatient and inpatient settings increased by 9.55% (p < 0.001) and 6.31% (p < 0.001), respectively. The volume changes in non-volume based purchased (non-VBP) drugs differed between outpatients and inpatients. The proportion of non-VBP drugs immediately increased by 5.34% (p = 0.002) overall, and showed an upward trend in the outpatient setting specially (p < 0.001) during the post-intervention period. However, no significant differences were observed in the proportion of non-VBP drugs in inpatient setting (p > 0.05) in term of level change (p > 0.05) or trend change (p > 0.05). The average per-visit expenditures of outpatients across all drug groups exhibited an upward trend (p < 0.05) post policy intervention. In addition, a similar increase in the overall costs for chemical drugs were observed in inpatient settings (coefficient = 2,599.54, p = 0.036), with no statistically significant differences in the regression slope and level (p = 0.814).Conclusion: The usage proportion of bid-winning drugs increased significantly post policy intervention, indicating greater use of bid-winning drugs and the corresponding substitution of non-winning hypertensive drugs. Drug expenditures for outpatients and health expenditures per visit for inpatients also exhibited an upward trend, suggesting the importance of enhanced drug use management in Traditional Chinese Medicine hospital settings.